Effects of final bleaching stage using hydrogen peroxide (Eq.) and peracetic acid in the ECF bleaching of acacia DED kraft pulps - Ermawan, Dede; Basta, Jiri.; Nazhad, Mousa M.; Lehtinen, Esa; PT. Riau Andalan Pulp and Paper, Indonesia (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
Effects of final bleaching of D 0 E OP D 1 acacia kraft pulp using various bleaching chemical such as chlorine dioxide, hydrogen peroxide and per acetic acid (eq.) had been studied in laboratory scale. Raw material used D 0 EOP pulp was taken from fiber line 1 of PT. Riau Andalan Pulp and Paper, Indonesia. D 0 EOP pulp was bleached by D 1 stage in specific condition to obtain optimal chemical charge to prod uce three kinds of specific brightness pulps namely 85, 87, 89% ISO. Henceforth, these pul ps will be referred to A pulp, B pulp, and C Pulp respectively. Afterward, Each D 1 pulp was final bleached by chlorine dioxide, hydrogen peroxide, and peracetic acid (eq.) in spec ific condition to obtain optimal chemical charge to produce 90% brightness pulps. La rger amount of final bleached pulps were produced for chemical analysis, optical and ph ysical properties. Bleaching filtrate was also collected to perform environmental paramet er analysis such as COD and TSS. Effect of beating on final bleached pulp was also s tudied by applying 0, 2000, and 4000 beating revolution. As comparison, mill D 2 pulp was also involved in all stages of properties measurement. In bleaching of chlorine dioxide 1 (D 1 ), three chemical charges had been obtained to produce A, B and C pulps those are respectively 1.5 , 2.5 and 9 kg active chlorine/tp. In bleaching of chlorine dioxide 2 (D 2 ), demand of chemical to achieve 90% ISO brightness is 10, 9, and 1.5 kg active chlorine/tp respectivel y for A, B and C pulp. Meanwhile, demand of hydrogen peroxide charge is 6, 4 and 1.5 kg/tp. While, Demand of chemical in PAA stage is unreachable target for A pulp, 2 kg/tp for B pulp and <1 kg/tp for C pulp. In the end of PAA bleaching, residual of hydrogen pero xide can be found in considerable amount due to hydrogen peroxide is inert in low pH and temperature, therefore, it can be extent utilized by adding more retention time and p H change to more alkaline condition, as a result, demand of chemical in PAA/P to achieve br ightness target is 1.5 kg/tp and 1 kg/tp for A and B pulp respectively. Brightness reversions of DPAA/P pulps are lower tha n DD, DP or DPAA pulps. There is not significant effect of different initial D 1 pulp brightness on fully bleached pulp brightness reversion; average % reversion is -2.04% , -2.51%, -1.50%, -1.32%, and -1.62% respectively for mill D 2, DD, DP, DPAA/P, and DPAA pulps. Generally, there i s no major different on strength properties and fiber morpholo gy among final bleached pulps. However, extractive content in alkaline conditioned bleaching decrease significantly compare to acidic conditioned bleaching, as a resul ts, DPAA/P pulps contain the lowest extractive, while DD pulps contain the highest extr active. The average extractive content is 0.26%, 0.31%, 0.08%, 0.05%, and 0.10% respectively for Mill D 2 , DP, DPAA/P, and DPAA. Moreover, even though P stage contributes to give higher COD and SS and D stage gives also higher chloride and SS, but compare to BAT in bleaching it was still acceptable. In addition, preliminary study on cost based on che mical demand and price shows that DP and DPAA/P stages are significantly more expensive, while cost of DPAA maybe of interested when comparing with DD.
A thesis submitted in partial fulfillment of the re quirement for the degree of Master of Science in Pulp and Paper Technology
Thesis (M. Sc.) - Asian Institute of Technology, 2011
Keywords: Kraft pulping process; Wood-pulp -- Bleaching